(untitled) (Texas Journal of Medical Science, 2022)
Background: Jaundice is observed in first week of life in 60% of term & 80% of preterm infants, it is usually benign, but untreated, severe indirect hyperbilirubinemia is potentially toxic to nervous system of neonate. Aim of the study: Identify the factors affecting the lines of management of neonatal jaundice. Patients &Methods: this cross sectional study was carried out at neonatal intensive care unit (NICU) of Children’s Hospital in the City of Kirkuk, Iraq; from May 2020 to November 2020.Data were collected from228 admission records. The age of patients were 1 day to 28 days. Results: from 228 neonate ,166(72%) had neonatal jaundice,128(77.1%)were term ,38(22.8%) were preterm, the factors studied were (level of total serum bilirubin TSB ,term ,preterm ,age of neonate ,& weight) with lines of management used in NICU (phototherapy ,antibiotics ,combined phototherapy with antibiotics ,& exchange transfusion ).There was a significant association between these factors & the lines of management applied . Conclusion: level of serum bilirubin is the most important factor in the management and the study showed a significant association between level of serum bilirubin and the other factors studied with the lines of management Recommendation: Educating families about early recognition of jaundice &seeking medical advice is important to avoid invasive procedures like exchange transfusion and it is be better to start phototherapy earlier &at lower TSB level in low birth weight babies